Inquisição no Pernambuco Quinhentista: o caso de Felícia Tourinho - CRUZ, Roberta Cristina da Silva (Universidade Federal do Pará, 2019)
The Tribunal of the Holy Office in Portugal was created in 1536 to investigate and punish crimes against the Catholic faith. Inquisitorial agents acted in the reorganization of the religious life, as in "inspection of faith". In Portuguese America, despite the lack of an Inquisitorial Tribunal, was developed the same goals as the kingdom through visitations and a network of agents established in different regions of the colony. This article aims to relate aspects of the First Visitation of the Holy Office to the actions on the repression of offenses related to deviations of faith. In this sense, we will divide our analysis into two parts: First we'll analyze how the Inquisition acted to suppress such deviations, and then, the case of Felicia Tourinho, indicted by divination practices. We will also examine how the Portuguese Inquisition dealt with this type of offence.